1996
DOI: 10.1177/0361198196153500101
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Material Functions and the Structure of Asphalts

Abstract: A simple model of the complex modulus, based on the general principles for a linear response function, is presented. The model represents a generalization of the Maxwell model and it is indicated that the model well describes a relatively broad group of regular and modified asphalts. A discrete spectrum of no more than 10 relaxation times is obtained for all the asphalts studied. The spectra of modified asphalts indicate the presence of several relaxation times that can be related to the interface interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…In 1990s, it was shown that the parameters of the calibration equation depend not only on the method used to determine the molecular weight, but also on the type of base asphalt used. 6,13,16 Roughly speaking, K $ 3 and α $ 0.1 for conventional unmodified asphalts can be used. Here, we use the calibration equation given by Themeli et al, 19 log MWÃ ð Þ= 2:…”
Section: Experiments and The Numerical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 1990s, it was shown that the parameters of the calibration equation depend not only on the method used to determine the molecular weight, but also on the type of base asphalt used. 6,13,16 Roughly speaking, K $ 3 and α $ 0.1 for conventional unmodified asphalts can be used. Here, we use the calibration equation given by Themeli et al, 19 log MWÃ ð Þ= 2:…”
Section: Experiments and The Numerical Resultsmentioning
confidence: 99%
“…It is known, that when conventional asphalt B with its high-penetration value (low viscosity) was modified by polymers and some additives, the graph of f(MW*) had the potential to contain at least one negative peak. 6,10,13,16 Such peaks are not artifacts that can be eliminated by a "proper" baseline. The negative peaks of f(MW*) were identified by Stastna et al 10 by the general model of the complex modulus.…”
Section: Experiments and The Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations